The Development Of Seat Posture Monitoring System - Mohd Zukhi, Nur Afifah Hani (IRC, 2019)
Nowadays, people are having a backbone problem because of their sitting posture is wrong. Even the health mobile application which was ‘Seat Posture’ is developed, but still occurs few problems. The first problem is the existing mobile application was only applicable to Android users. It caused the iOS users to be neglected. The second problem is where the existing product has only few features which is displaying the position of posture. The third problem is the existing application cannot run in background. It means that the application needed to be opened all the time or else the program will shut down. The solution for these problems is by developing new system which is ‘Seat Posture Monitoring System’. This system can help to detect body posture. If user sits with a wrong posture, a notification will be pushed and it displays ‘Sitting Posture is Wrong’ in the screen. The system will record at what time user sits with wrong posture. Besides, user can check on seat posture graph where it shows the graph when user sits with a correct or wrong posture. Other than that, there is a rating management where the sitting posture is rated. The rate will be recorded once user get the rating stars. For user who wants to know on how to sit with a correct posture, there are some tips provided by this system. The results are user can use this system to record all data and it can be as historical data if user wants to refer to the specialist doctor.